2016
DOI: 10.1021/acs.orglett.6b01336
|View full text |Cite
|
Sign up to set email alerts
|

Total Syntheses of Isowondonins Based on a Biosynthetic Pathway

Abstract: The first total syntheses of (-)-isowondonin A and (-)-isowondonin B, which are unusual imidazole marine alkaloids, has been accomplished through the development of methods for the selective formation of styryl sulfate group and regioselective alkylation of the imidazole. Application of the Noyori asymmetric hydrogenation of ketones allows the asymmetric synthesis. These results in conjunction with ECD calculations led to the determination of the absolute configuration of isowondonins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The 1 H NMR spectrum of 1 showed the presence of a 1,2,4-trisubstituted benzene ring [δ H 6.64, 6.32 (each 1H, d, J = 7.7 Hz) and 6.33 ppm (1H, s)], a 1,2,4,5tetrasubstituted benzene ring [δ H 6. (Figure 1). Based on the analysis of the 1 H− 1 H COSY, HSQC, and HMBC spectra, all the 1 H and 13 C NMR chemical shifts of 1 were assigned as shown in Tables 1 and 2. In the NOESY spectrum (Figure S1, Supporting Information), there were correlations between H-1 and H2′/H-6′, but no correlations were observed between H-1 and H-2/H-3, indicating that H-1 has an orientation different from that of H-2 and H-3, and H-1 was arbitrarily assigned in an α-orientation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 H NMR spectrum of 1 showed the presence of a 1,2,4-trisubstituted benzene ring [δ H 6.64, 6.32 (each 1H, d, J = 7.7 Hz) and 6.33 ppm (1H, s)], a 1,2,4,5tetrasubstituted benzene ring [δ H 6. (Figure 1). Based on the analysis of the 1 H− 1 H COSY, HSQC, and HMBC spectra, all the 1 H and 13 C NMR chemical shifts of 1 were assigned as shown in Tables 1 and 2. In the NOESY spectrum (Figure S1, Supporting Information), there were correlations between H-1 and H2′/H-6′, but no correlations were observed between H-1 and H-2/H-3, indicating that H-1 has an orientation different from that of H-2 and H-3, and H-1 was arbitrarily assigned in an α-orientation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Salviachinensine B (2), isolated as a white powder, gave the molecular formula C 18 H 18 O 7 , based on the 13 1 and 2) indicated the presence of a methoxy group and 17 other carbon atoms, including a carbonyl, 12 aromatic carbon atoms, a pair of double-bond carbon atoms, an oxygenated methine, and a methylene. Furthermore, the presence of a 3-(3,4-dihydroxyphenyl)-2-hydroxy-1-one system bearing a methoxy group at the carbonyl carbon (a tanshinol methyl ester moiety, Figure 1) was indicated by the resonances at δ C 174.3 (C-9), 71.6 (C-8), and 39.7 ppm (C-7) in the 13 C NMR spectrum.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…546 Renieramycin T 547 has been made, 548,549 while the absolute congurations of isowondonins A 1008 and B 1009, 550 isolated from Poecillastra wondoensis, were established following their syntheses. 551 Other rst total syntheses of hyrtinadine B, 552,553 dictyodendrin H and I, 554,555 crambescin A and C, 556,557 clavatadine C, 558,559 cyclosmenospongine, 560,561 strongylophorine 1, 2, 3, 562 8, 563 and 9, 564,565 arenaran A and B, 566,567 polyrhaphin D, 568,569 hamigeran D, 570 579 as has the side-chain conguration of clathsterol 1012. 580,581 A detailed combination of genomic and metagenomic analyses has shown that the biosynthesis of polytheonamide (Theonella swinhoei), 582 a member of the growing class of Ribosomally synthesised and Post-translationally modied Peptides (RiPPs), includes the rst example of a B 12 -dependent radical S-adenosylmethionine C-methylation step.…”
Section: Spongesmentioning
confidence: 99%
“…In the same year, Kim et al., introduced cis ‐styryl sulfonated catechol derivatives 222 as suitable 1,4‐bisnucleophiles for the first total synthesis of imidazole natural products (−)‐isowondonin A ( 223 ) and (−)‐isowondonin B ( 224 ) (Scheme A). Catechol derivative 222 was condensed with highly reactive α,α‐dibromoketone 225 in presence of Cs 2 CO 3 at 50 °C to give the 1,3‐dioxolane 225 a .…”
Section: The Gem‐dihaloketones In the Synthesis Of Heterocyclic Framementioning
confidence: 99%